KOMENTAR KASAR NETIZEN UNTUK VIDEO DEBAT FINAL PILKADA DKI 2017 DI CHANNEL YOUTUBE (Studi Etnografi Virtual tentang Komentar Kasar Netizen untuk Video Debat Final Pilkada DKI 2017 di Channel YouTube CNN Indonesia) - Rachmaniar Rachmaniar (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2017)
The purpose of this research is to know the rough netizen comments related video Debat Final Pilkada DKI 2017 on the YouTube channel CNN Indonesia. The method used in this study is a qualitative method with a virtual ethnography approach to analyze rough comments netizen related video Debat Final Pilkada DKI 2017 on the YouTube channel CNN Indonesia. The main object of this research is video Debat Final Pilkada DKI 2017 on the YouTube channelÂ of CNN Indonesia. Data collection techniques are conducted through participatory observation and literature studies. The results of this study indicate that rough netizen comments related video Debat Final Pilkada DKI 2017 on the YouTube channel of CNN Indonesia are: 1) netizens often insulting candidate pairs that are not his choice; 2) netizens mutually insulting other netizens supporting one candidate pair; and 3) netizens argue with other netizens related to their candidate pairs.